Efficiency to reach age of puberty and behaviour of buffalo heifers (Bubalus bubalis) kept on pasture or in confinement. (30th July 2014) - Sabia, E.; Napolitano, F.; De Rosa, G.; Terzano, G. M.; Barile, V. L.; Braghieri, A.; Pacelli, C.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to evaluate the influence of rearing system (free-ranging (FR) v. confinement (C)) on buffalo heifer efficiency to reach age of puberty and on behavioural and immune functions, two experiments were conducted from September 2010 to October 2011. In Experiment I, 32 subjects aged 8 to 9 months at the start of experiment were used. A total of 16 animals (group C) were group housed in an indoor slatted floor pen (4 m2/animal) with an outdoor paddock (4 m2/animal); 16 others grazed on a Mediterranean natural pasture of 40 ha (group FR). Behavioural data were collected and organic matter digestibility, blood metabolites and progesterone were determined. At the end of the experiment, a novel object test and a skin test were conducted, and the avoidance distance (AD) at the manger was measured. Free-ranging animals were able to express natural behaviours such as wallowing and grazing. C animals devoted more time to the novel object than FR animals, whereas AD at manger was lower in group FR than in group C (P<0.01). Cellular immune response was higher in FR heifers than in C animals (P<0.01). FR animals also showed a higher digestibility of organic matter (P<0.01). Heifers from group FR had higher plasma concentrations of non-esterified fatty acids (P<0.001) and lower concentrations of glucose than heifers from group C (P<0.001). C animals showed higher daily weight gains (P<0.01) and weight at the puberty (P<0.05), but there were no differences in terms of age of puberty between the two groups. The intakes of dry matter (DM), CP and energy to reach the age of puberty were similar in both groups. In order to verify whether the results obtained in Experiment I could be replicated in different rearing conditions (reduced pasture availability, different location and altitude), a second experiment was conducted on 26 animals, where only onset of age of puberty and metabolic profile were monitored. In Experiment II, 13 heifers grazed on a natural pasture of 5 ha, other 13 received the same space as indicated for Experiment I. Results from Experiment II generally confirmed those of Experiment I. Only the intakes of DM and energy to reach the age of puberty were higher in group C than in FR (P<0.001). A lower competition with human nutrition, reproductive performances similar to those shown by confined animals and the indications given by immune and behavioural variables, suggest that a free-range-based system may be conveniently used for buffalo heifer farming purposes.